DESCRIPTION OF LOW DENSITY LIPOPROTEIN (LDL) LEVELS AND FASTING COMPLIANCE IN OUTPATIENT CARDIAC PATIENTS AT RSU PRIMA MEDIKA DENPASAR IN THE MONTHS OF FEBRUARY TO MARCH 2025 - Ni Putu Martiana Prawita Sari; Nyoman Sudarma; Didik Prasetya (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Cardiovascular disease remains a leading cause of death both globally and nationally, with Low Density Lipoprotein(LDL) levels serving as a key biochemical indicator in the screening and management of heart disease. Accurate LDL testing requires adherence to pre-analytical procedures, particularly fasting for 10-12 hours. This study aimed to describe LDL levels and fasting compliance among outpatient cardiac patients at RSU Prima Medika Denpasar. A descriptive cross-sectional design was used with purposive sampling, involving 35 cardiac outpatients from February to March 2025. Data were collected through interviews and laboratory examinations using the Furuno CA-270 device. Results showed that 71% of respondents had LDL levels >100 mg/dL, indicating high levels, while 29% hadnormal levels (<100 mg/dL). All respondents (100%) complied with the fasting requirement. These findings indicate that high LDL levels are still commonly found among outpatient cardiac patients, particularly in productive-age males. The high level of fasting compliance reflects the effectiveness of pre-analytical patient education. This study emphasizes the importance of routine lipid screening and continuous education to enhance laboratory diagnostic accuracy and prevent cardiovascular complications.